A time domain method for wheel-rail force identification of rail vehicles. Issue 3 (4th March 2022) - Zhu, Tao; Wang, Xiao-rui; Fan, Yi-wei; Wang, Ming-meng; Zhang, Jing-ke; Xiao, Shou-ne; Yang, Guang-wu; Yang, Bing
Abstract : Using dynamic load identification technology to identify the wheel-rail force of rail vehicles is an economical and convenient method for indirect measurement. In this paper an analytical load identification method is proposed. Firstly, based on the theory of structural dynamics, the Duhamel integral is applied, combined with the characteristics of the rail vehicle system, to derive the analytical load identification method. Secondly, the correctness of the method is verified by a multi-degree-of-freedom system with exact solution. Next, a detailed vehicle dynamics simulation model is established as a virtual test vehicle and source of virtual measurements of the vehicle responses (axlebox accelerations). Different operating conditions are considered, and the virtual acceleration measurements are used as input to the load identification method for indirect measurement of the wheel-rail forces. Finally, the identified vertical and lateral wheelset force, vertical force of the left and right wheels, derailment coefficient and wheel unloading rate are compared with the corresponding time-histories from the virtual test-vehicle simulations. A good agreement is found with all of their correlation coefficients above 0.8. This result has important implications on the safety evaluation of vehicle curve negotiation by using acceleration measurements only, without the need for direct force measurements.